Uncertainty and Economic Activity: A Global Perspective - Ambrogio Cesa-Bianchi; M. Hashem Pesaran; Alessandro Rebucci (Inter-American Development Bank (IDB), 2014)
The 2007-2008 global financial crisis and the subsequent anemic recovery have rekindled academic interest in quantifying the impact of uncertainty on macroeconomic dynamics. This paper studies the interrelation between financial markets volatility and economic activity assuming that both variables are driven by the same set of unobserved common factors and that these factors affect volatility and economic activity with a time lag of at least a quarter. Under these assumptions, the paper analytically shows that volatility is forward looking and that the output equation of a typical VAR estimated in the literature is mis-specified. The paper empirically documents a statistically significant and economically sizable impact of future output growth on current volatility, and no effect of volatility shocks on business cycles, over and above those driven by the common factors. The evidence is interpreted as suggesting that volatility is a symptom rather than a cause of economic instability.
hdl:11319/6605
Keywords: E44; F44; G15; 330; Uncertainty; Realized volatility; GVAR; Great Recession; Identification; Business Cycle; Common Factors